Preparation method of bio-based bi-crosslinking hydrogel for capturing Fe < 3 + >
By using bio-based double crosslinked hydrogel SCG-PAAM in the printing and dyeing wastewater treatment, Fe3+ adsorption and Fenton reaction degradation, organic matter, the problem of Fe3+ removal in the printing and dyeing wastewater is solved, and efficient removal and resource recycling are achieved.
Patent Information
- Application Number
- CN202510019013.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-15
AI Technical Summary
Printing and dyeing wastewater contains a large amount of trivalent iron ions (Fe3+), which poses a threat to the water ecosystem. It is difficult for the existing technology to remove efficiently and recycle resources.
A bio-based bi-crosslinked hydrogel SCG-PAAM synthesized by a two-step method was prepared by a combination of sodium carboxymethylcellulose, γ-polyglutamic acid and acrylamide acrylic acid copolymer, and a hydrogel with high adsorption performance and mechanical stability, and was reused by Fenton reaction after adsorption saturation.
The efficient adsorption and removal of Fe3+ in the printing and dyeing wastewater was achieved, and the adsorption equilibrium was achieved within 30 minutes, with a removal rate of 97%. At the same time, the organic matter in the wastewater is degraded through the Fenton reaction, and the recycling of resources is realized.
Smart Images

Figure CN119819267A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for capturing Fe 3+ The invention discloses a method for preparing a bio-based double-cross-linked hydrogel, which specifically belongs to the field of water treatment such as printing and dyeing wastewater. Background Art
[0002] Driven by globalization, the printing and dyeing industry has developed rapidly, but it has also brought serious environmental problems, especially the pollution of printing and dyeing wastewater. These wastewaters contain a large amount of organic pollutants and heavy metal ions, such as trivalent iron (Fe 3+ ), posing a threat to aquatic ecosystems. To meet these challenges, the government and industry organizations are promoting printing and dyeing enterprises to adopt clean production technologies and strengthen wastewater treatment.
[0003] Among many wastewater treatment technologies, adsorption has attracted attention due to its simplicity, high efficiency and low cost. The properties of the adsorbent determine the effect of the adsorption process. As a new type of polymer material, hydrogel shows advantages in treating heavy metal ions. Sodium carboxymethyl cellulose (CMC), as a raw material for hydrogel, is favored due to its low cost, high adsorption capacity and stability. The adsorption performance and mechanical stability of hydrogel can be further improved by combining γ-polyglutamic acid (γ-PGA) and acrylamide acrylic acid copolymer (PAAM).
[0004] For example, Chinese patent CN 118649658A discloses "a heavy metal ion adsorption and its preparation method and application". First, banana peels are crushed into a first banana peel powder and a second banana peel powder. Then the first banana peel powder is treated with continuous impregnation of a sulfonate solution and an iron-containing solution to prepare a first modified banana peel powder. The second banana peel powder is first impregnated with an ammonium formate solution, then impregnated with an ethyl orthosilicate ethanol solution, and then dried after hydrolysis treatment under alkaline conditions, and finally washed with water to neutrality to prepare a second modified banana peel powder. Finally, the two modified banana peel powders are pyrolyzed to obtain an efficient heavy metal ion adsorbent. This adsorbent utilizes the pore structure and functional groups of banana peel powder to adsorb heavy metal ions in water through a variety of action mechanisms (such as reduction, complexation and precipitation). Compared with the traditional method, this method constructs a disordered and jagged pore structure, which improves the number of reusable times and processing efficiency of the adsorbent. For example, Chinese patent CN 104310568A discloses "a method for sewage treatment using Fenton reaction". First, water-soluble monomers, water-soluble crosslinking agents, emulsifiers and initiators are added to the aqueous dispersion of ferroferric oxide nanoparticles and used as the aqueous phase. Subsequently, a hydrophobic organic solvent is added, and then a reducing agent is added. The mixture is stirred to form an oil-in-water high internal phase emulsion. The emulsion is poured into a chromatography column, and the monomers are polymerized to obtain a porous column loaded with ferroferric oxide nanoparticles. The porous column can undergo Fenton reaction to degrade organic matter, and can effectively avoid leakage of nanoparticles and be recycled for multiple times.
[0005] The SCG-PAAM double cross-linked hydrogel developed in this study can effectively adsorb iron ions in printing and dyeing wastewater, and after adsorption saturation, it can be reused through the Fenton reaction to degrade organic matter in the wastewater. This two-step treatment strategy improves the wastewater treatment efficiency, realizes resource recycling, conforms to the concept of sustainable development, and provides a new solution for printing and dyeing wastewater treatment. Summary of the invention
[0006] The purpose of the present invention is to provide a method for capturing Fe 3+ The preparation method of bio-based double cross-linked hydrogel is proposed. The SCG-PAAM double cross-linked hydrogel synthesized by a two-step method can not only effectively adsorb iron ions in printing and dyeing wastewater, but also the gel material after adsorption saturation can be used as a catalyst for secondary utilization through the Fenton reaction to degrade organic pollutants in the wastewater.
[0007] The technical solution of the present invention is:
[0008] Step 1: prepare a sodium carboxymethyl cellulose solution. Add a certain amount of sodium carboxymethyl cellulose powder into a NaOH solution, let it stand for a period of time at room temperature and stir it thoroughly to obtain a sodium carboxymethyl cellulose aqueous solution.
[0009] Step 2: prepare a mixed prepolymer solution. Add a certain amount of γ-polyglutamic acid powder to the sodium carboxymethyl cellulose aqueous solution prepared in step 1, stir for a period of time, then add ethylene glycol diglycidyl ether as a cross-linking agent, continue stirring for a period of time to obtain a uniform prepolymer solution.
[0010] Step 3: Prepare foamable sodium carboxymethyl cellulose / γ-polyglutamic acid SCG hydrogel. Add a certain amount of foaming agent sodium dodecyl sulfate SDS to the prepolymer solution of step 2. After stirring for a period of time, put it in a constant temperature and humidity chamber for cross-linking for a period of time to form a foamable sodium carboxymethyl cellulose / γ-polyglutamic acid SCG hydrogel.
[0011] Step 4: prepare a PAAM mixed solution. Add a certain amount of acrylamide AM and acrylic acid AA into deionized water, stir evenly at room temperature, and then add a certain amount of N,N′-methylenebisacrylamide MBA and ammonium persulfate APS to prepare a PAAM mixed solution.
[0012] Step 5: Prepare a double-crosslinked SCG-PAAM hydrogel. Immerse the SCG hydrogel prepared in step 3 in the PAAM mixed solution prepared in step 4 under low temperature conditions for a period of time until the solution is completely absorbed by the SCG hydrogel. Store it in a constant temperature and humidity chamber for a period of time, and then rinse it with deionized water until the hydrogel becomes neutral. Then freeze-dry it for a period of time to obtain a hydrogel for capturing Fe 3+Bio-based double-cross-linked hydrogel.
[0013] Furthermore, in step 1, the molar concentration of the NaOH solution is 0.2 mol / L, the mass concentration of sodium carboxymethyl cellulose is 3-5%, the temperature is 25° C., the standing time is 12-24 h, the stirring temperature is 20-25° C., and the stirring time is 1-2 h.
[0014] Furthermore, in step 2, the mass concentration of γ-polyglutamic acid is 1-2%, the mass concentration of ethylene glycol diglycidyl ether is 10-20%, the stirring temperature is 20-25° C., and the stirring time is 4-6 h.
[0015] Furthermore, in step three, the molar concentration of SDS is 5-15 mmol / L, the stirring time is 4-6 hours, the temperature of the constant temperature and humidity chamber is 50-70° C., the humidity is 80-100%, and the cross-linking time is 2-4 hours.
[0016] Furthermore, in step 4, the mass concentration of AM is 1-3%, the mass concentration of AA is 1-3%, and the mass concentrations of MBA and APS are 2-8%.
[0017] Furthermore, in step five, the low temperature condition is 0-10°C, the soaking time is 2-10h, the temperature of the constant temperature and humidity chamber is 40-80°C, the humidity is 80-100%, the insulation time is 2-4h, and the freeze-drying time is 40-60h.
[0018] The advantages of the present invention are:
[0019] The selected sodium carboxymethyl cellulose has shown significant advantages in the field of water treatment, with low production costs and abundant adsorption sites. In addition to containing a large number of adsorption groups, the selected γ-polyglutamic acid also has super strong adhesion and can be used as a flocculant to increase the removal of heavy metal ions. The selected sodium dodecyl sulfate greatly increases the porosity of the hydrogel, shortens the adsorption path, and allows the adsorption to quickly reach equilibrium. The selected hydrogel network of acrylamide and acrylic acid copolymer can provide good mechanical strength and flexibility, which is convenient for separation and recovery from wastewater. The experiment adopts a simple method of first preparing a network and then using an immersion process to form a second network, and the experiment is easy to reproduce.
[0020] The present invention applies the excellent performance hydrogel SCG-PAAM to Fe 3+ The hydrogel showed the ability to efficiently and quickly remove trivalent iron ions. It can reach adsorption equilibrium in about 30 minutes, and the removal rate reaches 97%. More importantly, in order to achieve high-value applications of adsorption materials, Fe 3+ @SCG-PAAM is mixed with hydrogen peroxide as a catalytic material to generate hydroxyl radicals, which promotes Fe 3+ Reduction to Fe2+ The hydrogels soaked in hydroxylamine hydrochloride can decolorize the methylene blue dye within one minute. 3+ @SCG-PAAM can also achieve the same degradation effect after a few hours. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor.
[0022] Figure 1 This is the SEM image of Example 1.
[0023] Figure 2 This is the SEM image of comparative example three.
[0024] Figure 3 The hydrogels with different components have different 3+ Adsorption diagram.
[0025] Figure 4 For example, a pair of different initial concentrations of Fe 3+ Schematic diagram of wastewater adsorption.
[0026] Figure 5 Example 1: Fe at pH 2-6 3+ Adsorption diagram.
[0027] Figure 6 Example 1: Fe at a temperature of 25-50°C 3+ Adsorption diagram.
[0028] Figure 7 Example 1 Adsorption of Fe 3+ Finally, schematic diagram of the degradation of methylene blue dye as a catalyst.
[0029] Figure 8 Fe 3+ Schematic diagram of the cycle of @SCG-PAAM as a catalyst for the degradation of methylene blue dye. DETAILED DESCRIPTION
[0030] In order to make the above-mentioned objects, features and advantages of the present invention more clearly understood, the technical solutions of the present invention are further described below in conjunction with the accompanying drawings and embodiments. However, the present invention is not limited to the embodiments listed, and should also include any other known changes within the scope of the rights claimed by the present invention.
[0031] First, the "embodiment 1" referred to herein refers to a specific feature, structure or characteristic that can be included in at least one implementation of the present invention. Secondly, the present invention is described in detail using a structural schematic diagram, etc. When describing the embodiment of the present invention in detail, for the sake of convenience, the schematic diagram will not be partially enlarged according to the general proportion, and the schematic diagram is only an example, which should not limit the scope of protection of the present invention. In addition, in actual production, a three-dimensional space of length, width and depth should be included.
[0032] In addition, the abbreviations mentioned in the present invention are all fixed abbreviations in the field, and some of the abbreviations are explained as follows: CMC: sodium carboxymethyl cellulose; PGA: γ-polyglutamic acid; PAAM: acrylamide-acrylic acid polymer; SDS: sodium dodecyl sulfate (foaming agent); MBA: N, N'-methylenebisacrylamide; APS: ammonium persulfate; SEM: scanning electron microscope;
[0033] Embodiment 1
[0034] In this embodiment, a method for capturing Fe is prepared according to the following steps. 3+ Bio-based double-cross-linked hydrogel;
[0035] The first step is to prepare sodium carboxymethyl cellulose aqueous solution
[0036] A certain amount of sodium carboxymethyl cellulose powder was added to a NaOH solution with a molar concentration of 0.2 mol / L, and the solution was allowed to stand for 12 hours to allow it to fully dissolve, and then stirred at room temperature for 1 hour to obtain a sodium carboxymethyl cellulose aqueous solution with a mass concentration of 4%.
[0037] Step 2: Prepare mixed prepolymer solution
[0038] A certain amount of γ-polyglutamic acid powder was added to 4% sodium carboxymethyl cellulose as solvent and stirred for 1 hour. Then, 15% ethylene glycol diglycidyl ether was added as a cross-linking agent and stirred for 4 hours to form a uniform prepolymer solution.
[0039] Step 3: Preparation of SCG hydrogel
[0040] SDS with a molar concentration of 9 mmol was added to the prepolymer solution prepared above, stirred for 4 h, and cross-linked for 2 h in a constant temperature and humidity chamber at a temperature of 60° C. and a humidity of 90% to form a porous SCG hydrogel.
[0041] Step 4: Preparation of PAAM mixed solution
[0042] A certain amount of AA and AM were added to deionized water, and MBA and APS with a mass concentration of 5% were added, and stirred for 10 minutes to prepare a PAAM mixed solution with a mass concentration of 4%.
[0043] Step 5: Preparation of SCG-PAAM hydrogel
[0044] The PAAM mixed solution prepared in advance was placed at a low temperature of 4°C, and the SCG hydrogel was immersed in it. The mixture was kept for several hours until the solution was completely absorbed by the SCG hydrogel. The mixed gel was stored in a 60°C constant temperature and humidity chamber for 2 hours. After the reaction was completed, it was continuously rinsed with deionized water until the hydrogel was neutral. Finally, the dry SCG-PAAM hydrogel was obtained by freeze drying for 48 hours.
[0045] Comparative Example 1
[0046] In this embodiment, a method for capturing Fe is prepared according to the following steps. 3+ CMC hydrogel;
[0047] The first step is to prepare CMC solution.
[0048] A certain amount of CMC powder was added to a NaOH solution with a molar concentration of 0.2 mol / L, and the mixture was allowed to stand for 12 h and stirred at room temperature for 1 h to mix the mixture evenly, thereby obtaining a CMC solution with a mass concentration of 4%.
[0049] Step 2: Prepare a Fe 3+ CMC hydrogel
[0050] Using 4% sodium carboxymethyl cellulose as solvent, 15% ethylene glycol diglycidyl ether was added as a cross-linking agent, stirred at room temperature for 4 hours, and after being evenly mixed, placed in a constant temperature and humidity chamber, cross-linked for 2 hours in a constant temperature and humidity chamber at a temperature of 60°C and a humidity of 90% to form a CMC hydrogel.
[0051] Comparative Example 2
[0052] In this embodiment, a method for capturing Fe is prepared according to the following steps. 3+ CG hydrogel;
[0053] The first step is to prepare CMC solution.
[0054] A certain amount of CMC powder was added to a NaOH solution with a molar concentration of 0.2 mol / L, and the mixture was allowed to stand for 12 h and stirred at room temperature for 1 h to mix the mixture evenly, thereby obtaining a CMC solution with a mass concentration of 4%.
[0055] Step 2: Preparation of polymer mixed solution
[0056] A certain amount of γ-polyglutamic acid powder was added into sodium carboxymethyl cellulose with a mass concentration of 4% as solvent and stirred for 1 hour to form a uniform polymer mixed solution.
[0057] Step 3: Prepare a Fe 3+ CG hydrogel
[0058] Ethylene glycol diglycidyl ether with a mass concentration of 15% was added to the polymerization mixed solution as a cross-linking agent, and stirring was continued for 4 hours. The CG hydrogel was formed by cross-linking for 2 hours in a constant temperature and humidity chamber at a temperature of 60° C. and a humidity of 90%.
[0059] Comparative Example 3
[0060] In this embodiment, a method for capturing Fe is prepared according to the following steps. 3+ CG-PAAM hydrogel;
[0061] The first step is to prepare CMC solution.
[0062] A certain amount of CMC powder was added to a NaOH solution with a molar concentration of 0.2 mol / L, and the mixture was allowed to stand for 12 h and stirred at room temperature for 1 h to mix the mixture evenly, thereby obtaining a CMC solution with a mass concentration of 4%.
[0063] Step 2: Preparation of polymer mixed solution
[0064] A certain amount of γ-polyglutamic acid powder was added into sodium carboxymethyl cellulose with a mass concentration of 4% as solvent and stirred for 1 hour to form a uniform polymer mixed solution.
[0065] Step 3: Prepare a Fe 3+ CG hydrogel
[0066] Ethylene glycol diglycidyl ether with a mass concentration of 15% was added to the polymerization mixed solution as a cross-linking agent, and stirring was continued for 4 hours. The CG hydrogel was formed by cross-linking for 2 hours in a constant temperature and humidity chamber at a temperature of 60° C. and a humidity of 90%.
[0067] Step 4: Prepare PAAM mixed solution
[0068] A certain amount of AA and AM were added to deionized water, and MBA and APS with a mass concentration of 5% were added, and stirred for 10 minutes to prepare a PAAM mixed solution with a mass concentration of 4%.
[0069] Step 5: Prepare a method for capturing Fe 3+ CG-PAAM hydrogel
[0070] Under low temperature conditions of 4°C, the CG hydrogel was immersed in the PAAM mixed solution for several hours until the solution was completely absorbed by the CG hydrogel. The mixed gel was stored in a 60°C incubator for 2 hours. After the reaction was completed, it was continuously rinsed with deionized water until the hydrogel was neutral. Finally, the dry CG-PAAM hydrogel was obtained by freeze drying for 48 hours.
[0071] See also Figure 1 , Figure 1 A method for capturing Fe prepared in Example 1 3+ Schematic diagram of the bio-based double cross-linked hydrogel. As shown in the figure, due to the addition of SDS, the gel material has sufficient and large pores.
[0072] See also Figure 2 , Figure 2 A method for capturing Fe prepared in comparative example 3 3+ Schematic diagram of CG-PAAM hydrogel. As shown in the figure, the pores of the gel material without SDS are "blocked" during the process of absorbing the PAAM mixed solution.
[0073] See also Figure 3 , Figure 3 The results of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 are as follows: 3+ Schematic diagram of the adsorption capacity and removal rate of SCG-PAAM for Fe 3+ The adsorption capacity is the best and the removal rate is the highest.
[0074] See also Figure 4 , Figure 4 For example, a pair of different initial concentrations of Fe 3+ Schematic diagram of wastewater adsorption. As shown in the figure, as the initial concentration of the solution increases, the adsorption capacity of the hydrogel increases from 11.77 mg·g -1 Increased to 80.41 mg g -1 .
[0075] See also Figure 5 , Figure 5 Example 1: Fe at pH 2-6 3+ Schematic diagram of adsorption. As shown in the figure, the adsorption capacity and removal rate will continue to increase with the increase of solution pH, from 23.69 mg·g -1 Increased to 49.11 mg g -1 , increased from 47.37% to 98.20%.
[0076] See also Figure 6 , Figure 6 Example 1: Fe at a temperature of 25-50°C 3+ Schematic diagram of the adsorption of Fe 3+ The adsorption capacity and removal rate showed an increasing trend with the increase of temperature.
[0077] In order to achieve high-value applications of SCG-PAAM hydrogels after adsorption and reduce costs, the captured Fe 3+The hydrogel Fe 3 + @SCG-PAAM is used as a catalyst to mix with H2O2 to produce hydroxyl radicals, which 3+ Converted to Fe 2+ , methylene blue dye was degraded by Fenton reaction.
[0078] See also Figure 7 , Figure 7 Fe 3+ @SCG-PAAM, schematic diagram of the degradation of methylene blue dye as a catalyst. As shown in the figure, the hydrogel was soaked with ammonium hydrochloride (the Fe 3+ Reduction to Fe 2+ ), after adding 1mL of H2O2, the methyl blue solution was degraded within one minute, causing it to fade quickly. The hydrogel that was not soaked in ammonium hydrochloride also achieved the same effect after 6 hours.
[0079] See also Figure 8 , Figure 8 Fe 3+ Schematic diagram of the cycle of @SCG-PAAM as a catalyst for the degradation of methylene blue dye. As shown in the figure, Fe 3+ @SCG-PAAM as a catalyst has the ability to be continuously recycled. And the cyclic adsorption test shows that the hydrogel still has the ability to degrade methyl blue after five cycles.
[0080] It should be noted that the above embodiments and comparative examples are only used to illustrate the technical solutions of the present invention, rather than to limit the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A method for capturing Fe 3+ A method for preparing a bio-based double-crosslinked hydrogel, characterized in that: The method comprises the following steps: firstly, adding a certain mass of sodium carboxymethyl cellulose powder into a sodium hydroxide solution, stirring it for a period of time at a certain temperature until it is dissolved, so as to obtain a sodium carboxymethyl cellulose solution; adding gamma-polyglutamic acid powder into the prepared sodium carboxymethyl cellulose aqueous solution, stirring it for a period of time at a certain temperature, then adding ethylene glycol diglycidyl ether as a crosslinking agent, continuing to stir it for a period of time at a certain temperature, so as to obtain a uniform prepolymer solution; secondly, adding a foaming agent sodium dodecyl sulfate SDS into the prepolymer solution, stirring it evenly, and then placing it in a certain temperature and humidity range. The method comprises the following steps: cross-linking for a period of time in a constant temperature and humidity chamber to form a porous foamed sodium carboxymethyl cellulose / γ-polyglutamic acid SCG hydrogel; then the SCG hydrogel is immersed in a PAAM mixed solution containing N, N′-methylenebisacrylamide, ammonium persulfate, acrylamide, and acrylic acid under low temperature conditions for a period of time until the solution is completely absorbed by the SCG hydrogel; the SCG hydrogel is then placed in a constant temperature and humidity chamber for a period of time, and after the reaction is completed, the hydrogel is continuously rinsed with deionized water until the hydrogel becomes neutral, and finally freeze-dried for a period of time to obtain a hydrogel for capturing Fe. 3+ Bio-based double-cross-linked hydrogel.
2. A method for capturing Fe according to claim 1 3+ A method for preparing a bio-based double-crosslinked hydrogel, characterized in that: The molar concentration of the sodium hydroxide solution in the sodium carboxymethyl cellulose solution is 0.2 mol / L, the mass concentration of the sodium carboxymethyl cellulose is 3-5%, the stirring temperature is 20-25° C., and the stirring time is 1-2 h.
3. A method for capturing Fe according to claim 1 3+ A method for preparing a bio-based double-crosslinked hydrogel, characterized in that: The mass concentration of the gamma-polyglutamic acid is 1-2%, the mass concentration of ethylene glycol diglycidyl ether is 10-20%, the stirring temperature is 20-25° C., and the stirring time is 4-6 hours.
4. A method for capturing Fe according to claim 1 3+ A method for preparing a bio-based double-crosslinked hydrogel, characterized in that: The molar concentration of the foaming agent sodium dodecyl sulfate SDS is 5-15 mmol / L, the gelling temperature of the SCG hydrogel is 50-70° C., the humidity is 80-100%, and the cross-linking time is 2-4 hours.
5. A method for capturing Fe according to claim 1 3+ A method for preparing a bio-based double-crosslinked hydrogel, characterized in that: In the PAAM mixed solution containing N,N'-methylenebisacrylamide, ammonium persulfate, acrylamide and acrylic acid, the mass concentration of acrylamide is 1-3%, the mass concentration of acrylic acid is 1-3%, and the mass concentration of N,N'-methylenebisacrylamide and ammonium persulfate is 2-8%; the low temperature condition is 0-10°C, and the immersion time is 2-10h.
6. A method for capturing Fe according to claim 1 3+ A method for preparing a bio-based double-crosslinked hydrogel, characterized in that: The temperature of the constant temperature and humidity box is 40-80°C, the humidity is 80-100%, the insulation time is 2-4h, and the freeze-drying time is 40-60h.
7. A method for capturing Fe obtained by the preparation method according to any one of claims 1 to 6. 3+ The bio-based double-crosslinked hydrogel is characterized in that It is specifically used in water treatment fields such as printing and dyeing wastewater.
Citation Information
Patent Citations
Wastewater treatment method by utilizing Fenton reaction
CN104310568A
Heavy metal ion adsorbent as well as preparation method and application thereof
CN118649658A